Multinational Companies and Waste Management in Africa : Responsible and Empowering Strategies - (:unkn) unknown (My University, 2024)
The problem of waste management in African countries is a growing one, and the responsibility for it generally lies with multinational companies. In fact, these companies contribute significantly to the generation of waste in these countries through the implementation of bottom on pyramid (BoP) strategies to penetrate poor markets. Our thesis highlights the role that multinational companies can play in the improvement of waste management resulting from their activities in African countries. This topic has received very little attention in the management science literature, although it raises a real strategic management problem for these multinational companies, which have made environmental commitments at global level and see their own branded packaging being dragged through the streets of developing countries. This prescriptive research suggests a taxonomy of responsible and empowering strategies for managing the waste generated by the activities of multinational companies in developing countries. To this purpose, we conducted qualitative research based on a multiple case study of two Nestlé subsidiaries located in Cameroon and South Africa. The choice of our two cases was justified by the contrasting nature of their context, even though they belong to the same firm. The comparative analysis of the two cases in the light of our conceptual framework based on the CSR bottom of pyramid made it possible to identify notable points of convergence and divergence in the development and implementation of responsible waste management strategies resulting from the activities of the multinational company in Africa. These strategies are built on the concepts of cooperation, inclusion and local embedding. We propose a taxonomy based on four forms of responsible and empowering waste management strategies: contributive strategies, supportive strategies, intermediate strategies and circular strategies.
Keywords: African Research